2013
DOI: 10.1007/s00572-013-0543-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil tillage on Tuber magnatum development in natural truffières

Abstract: Tuber magnatum Pico, the Italian white truffle, commands the highest prices of any truffle. Despite its commercial value, it is the only edible European truffle which has not yet been successfully cultivated. Because of this, it is essential to safeguard natural truffières and to identify cultural practices to maximize their productivity. Soil tillage is successfully and extensively used in black truffle cultivation to enhance productivity, but its effects are not known on the development of T. magnatum. A rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 41 publications
0
12
0
1
Order By: Relevance
“…Therefore, the changes in soil properties may affect the growth and mycorrhizal synthesis of T. indicum . The ectomycorrhizosphere soil in the present study was alkalescent, which is considered suitable for the cultivation of different varieties of truffles ( Garcia-Montero et al, 2008 ; Salerni et al, 2014 ). However, the ectomycorrhizosphere soil ( T. indicum mycorrhized with P. armandii ) was found slightly acidic in our previous study ( Li et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the changes in soil properties may affect the growth and mycorrhizal synthesis of T. indicum . The ectomycorrhizosphere soil in the present study was alkalescent, which is considered suitable for the cultivation of different varieties of truffles ( Garcia-Montero et al, 2008 ; Salerni et al, 2014 ). However, the ectomycorrhizosphere soil ( T. indicum mycorrhized with P. armandii ) was found slightly acidic in our previous study ( Li et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that T. magnatum mycelium is particularly abundant and widespread in spring and tends to concentrate in the productive areas during fruiting (autumn) (Iotti et al, 2014). Using this technique it was possible to assess the effects of cultural practices on T. magnatum and suggest methods for its future cultivation (Salerni et al, 2014). The same technique was also applied to detect and quantify T. melanosporum and T. aestivum mycelium in the soil (Gryndler et al, 2013b;Parladè et al, 2013).…”
Section: Ecological Studiesmentioning
confidence: 99%
“…Salerni et al (2014) report the effects of shallow tilling in a natural white truffle site on the quantity of white truffle mycelium detected in soil by real-time PCR methods. Their observations indicate that tilling improves soil porosity and increases the quantity of white truffle mycelium, while decreasing the overall ECM fungal species diversity.…”
Section: Purpose and Content Of This Special Issuementioning
confidence: 99%